2015
DOI: 10.1007/s00595-015-1206-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative independent prognostic factors in patients with borderline resectable pancreatic ductal adenocarcinoma following curative resection: the neutrophil-lymphocyte and platelet-lymphocyte ratios

Abstract: Higher preoperative NLR and PLR can be independent predictive risk factors in BR-PDAC patients following curative resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 41 publications
0
40
1
1
Order By: Relevance
“…Several inflammatory factors, such as plasma fibrinogen, neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR) are identified as useful indicators for predicting the prognosis in renal cell carcinoma, ovarian cancer, and hepatocellular carcinoma [46]. Recently, the preoperative platelet to lymphocyte ratio (PLR), which also reflects the degree of systemic inflammation, has been found to be linked to prognosis in patients with PC [79]. However, some studies failed to find correlation between PLR and prognosis of PC [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Several inflammatory factors, such as plasma fibrinogen, neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR) are identified as useful indicators for predicting the prognosis in renal cell carcinoma, ovarian cancer, and hepatocellular carcinoma [46]. Recently, the preoperative platelet to lymphocyte ratio (PLR), which also reflects the degree of systemic inflammation, has been found to be linked to prognosis in patients with PC [79]. However, some studies failed to find correlation between PLR and prognosis of PC [1012].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical relevance of this ongoing inflammatory program is reflected in poor outcomes correlated with infiltrating inflammatory cells and the contributions of specific cell types are being increasingly elucidated (10, 11). For instance, neutrophil-lymphocyte ratio may represent a prognostic marker in PDA patients with a lower ratio representing improved prognosis and, despite the lack of a significant increase in the total cell number, B-cells have now been implicated in PDA progression through their ability to impact myeloid cell function (1214). Meanwhile, single-agent inhibitors of immune checkpoints have not demonstrated substantial efficacy in PDA (15).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood leukocyte count is a simple and valuable indicator that can reflect the degree of systemic inflammatory response in tumor patients [20], and elevations of NLR, PLR, and MLR are thought to reflect an exaggerated systemic inflammatory response [6-8]. Asari et al [6] found that high PLR could be used as an independent prognostic risk factor in resectable pancreatic ductal carcinoma. Ding et al [7] showed that NLR was an independent predictor for colon cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The blood neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR) are systemic markers of inflammation. Strong evidence suggests that the NLR, PLR, and MLR are independent prognostic factors for survival in multiple tumors [6-8]. …”
Section: Introductionmentioning
confidence: 99%